Avaliação da qualidade de vida de pacientes com síndrome coronariana aguda pelo Whoqol-bref - Felice, Rosângela de Oliveira (2023)
Introduction: Cardiovascular diseases exhibit high rates of morbidity and mortality worldwide, leading to changes in the quality of life for patients and their social network. Objectives: Assessing the quality of life in patients diagnosed with acute coronary syndrome (ACS) using the WHOQOL-Bref instrument. Materials and Methods: 185 patients (all genders) with an average age of 57 years were included in this study. They were admitted to the emergency unit of the Clinical Hospital of the Federal University of Uberlândia with a confirmed cardiological diagnosis of ACS. Data collection took place from August 2018 to August 2021. The quality of life was assessed by administering the WHOQOL-Bref questionnaire at the initial medical visitand repeated six months after hospital discharge. Statistical analysis was performed using SPSS software version 20.0, employing Z statistics based on the paired Wilcoxon test, chi-square test, McNemar’s test, and Wald test. Results: ACS was confirmed in all volunteers, with unstable angina diagnosed in 4.3% of patients (n=8); acute myocardial infarction without ST segment elevation was found in 15.68%(n=29) of patients, while 80% (n=148) experienced myocardial infarction with ST segment elevation. Comparing the results of the two assessments (initial and after discharge), there was an improvement in quality of life related to the psychological domain, but a decline in the physical domain, specifically in aspects related to pain, mobility, work capacity, and personal relationships, including financial aspects and sexual activity. No significant impact was observed in the domain related to the environment. Conclusion: The obtained results indicate that the occurrence of ACS has negative consequences on quality of life, which were detected by the WHOQOL-Bref. These consequences had an impact on the physical and social relationship domains. Improvement in quality of life was found in the psychological domain